2009
DOI: 10.1016/j.neuron.2009.04.027
|View full text |Cite
|
Sign up to set email alerts
|

Instantaneous Modulation of Gamma Oscillation Frequency by Balancing Excitation with Inhibition

Abstract: SUMMARY Neurons recruited for local computations exhibit rhythmic activity at gamma frequencies. The amplitude and frequency of these oscillations are continuously modulated depending on stimulus and behavioral state. This modulation is believed to crucially control information flow across cortical areas. Here we report that in the rat hippocampus gamma oscillation amplitude and frequency vary rapidly, from one cycle to the next. Strikingly, the amplitude of one oscillation predicts the interval to the next. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

72
538
3
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 553 publications
(614 citation statements)
references
References 57 publications
(82 reference statements)
72
538
3
1
Order By: Relevance
“…3C). Given that prior experiments suggest cycle-by-cycle recruitment of inhibition after excitation in orchestrating high-frequency rhythms (20), it is likely that the origin of the observed fast rhythms in our experiment was either distal to the recorded region/layer or included a mixture of distal and focal elements. These possible distal contributions could be conveyed through afferents from different layers of the involved column or from neighboring areas.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…3C). Given that prior experiments suggest cycle-by-cycle recruitment of inhibition after excitation in orchestrating high-frequency rhythms (20), it is likely that the origin of the observed fast rhythms in our experiment was either distal to the recorded region/layer or included a mixture of distal and focal elements. These possible distal contributions could be conveyed through afferents from different layers of the involved column or from neighboring areas.…”
Section: Discussionmentioning
confidence: 88%
“…Mechanistically, it has been shown that the temporal interplay of synaptic excitation and inhibition (15) and the dynamic balance of ensemble excitation and inhibition (13) shape the neocortical network activity during different states [wakefulness, SWS, and rapid eye movement (REM)]. Specifically, studies of hippocampal and entorhinal cortex point to a link between phasic discharge of fast-spiking (FS) interneurons and the γ-cycle (16)(17)(18)(19), and show how the excitation/inhibition balance modulates γ-oscillations (20). Both experimental and simulation studies frame β-oscillations as inhibition-based rhythms as well (21,22).…”
mentioning
confidence: 99%
“…Third, GABA A receptors opposite PV cell terminals produce very rapid rising and decaying IPSCs. Loss of PV immunoreactivity because of a reduction in PV expression and actual loss of PV-positive cells has been implicated in a number of neuropsychiatric diseases and models associated with schizophrenia (65)(66)(67)(68). Although both are considered markers for loss of appropriate inhibition, it remains a matter of contention whether loss of PV protein or loss of the PV cells themselves generates the decreased immunoreactivity observed in the disease state.…”
Section: Role Of Disrupted Fast-phasic Inhibition In Reduced γ-Power mentioning
confidence: 99%
“…The frequency of gamma oscillation depends on the surrounding circuitry and its behavior (Atallah and Scanziani, 2009;Mann and Mody, 2010). Therefore, pair-by-pair variability of the peak frequencies might be expected to be larger in SUA-SUA coherence than those between MUAs or between MUA and LFP, since the variability of the surrounding circuit would be larger in the case of single-unit pairs compared with other configurations.…”
Section: Coherence and Granger Causalitymentioning
confidence: 99%